The impact of corruption on market reactions to international strategic alliances - Li, Chengguang; Reuer, Jeffrey J. (Journal of International Business Studies, 2022)
Drawing on institutional theory, we argue that the level of corruption in an alliance partner’s country negatively affects the market reaction to a focal firm’s international strategic alliance announcement, as corruption creates uncertainty regarding the behavior of the partner firm. We further propose that anti-bribery laws in the focal firm’s home country strengthen the negative relation between corruption and market reactions, while the focal firm’s experiences in challenging institutional environments potentially attenuate the relationship. Our empirical analysis covers more than 1,000 international strategic alliance announcements involving firms from 30 countries. The findings indicate the importance of corruption as a facet of the institutional environment that shapes firms’ value creation opportunities and risks in international alliances.